2006
DOI: 10.1017/s0265021506000639
|View full text |Cite
|
Sign up to set email alerts
|

Renal impact of fluid management with colloids: a comparative review

Abstract: Colloids display important differences in their actions on the kidney. These contrasting renal effects should be considered in making fluid management decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 119 publications
0
50
1
4
Order By: Relevance
“…10,[11][12][13][14]26,29 However, this was not supported by our study. During 2003 to 2013, HES solutions used at Helsinki University Hospital were all thirdgeneration solutions compared with the first-and second-generation solutions used in earlier studies.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…10,[11][12][13][14]26,29 However, this was not supported by our study. During 2003 to 2013, HES solutions used at Helsinki University Hospital were all thirdgeneration solutions compared with the first-and second-generation solutions used in earlier studies.…”
Section: Discussioncontrasting
confidence: 91%
“…Other studies have shown that gelatin does not have a significant role in kidney damage occurrence in septic elderly patients. 25 However, studies have reported gelatin to elevate postoperative creatinine levels 26 compared with crystalloids, indicating renal damage. This has also been demonstrated in studies where kidney function after liver transplant was studied with living donors.…”
Section: Discussionmentioning
confidence: 99%
“…Choice, timing, and amount of fluid administration are also emerging as important determinants of AKI, with some concerns raised over the use of certain forms of colloid, namely hydroxyethyl starch (31)(32)(33). In a randomized study of septic patients, Schortgen et al (34) found that patients who were randomly assigned to hydroxyethyl starch had a much higher risk for acute renal failure, oliguria, and higher peak creatinine than those who were randomly assigned to gelatin.…”
Section: Prevention/protection Strategiesmentioning
confidence: 99%
“…
Sir, Artificial colloids display nephrotoxicity, and the pathophysiological mechanisms are of considerable clinical interest [1]. In a cohort study report, Schortgen and collaborators [2] pose the question whether ''highoncotic forces rather than the chemical nature of fluids have a deleterious effect on renal function''.
…”
mentioning
confidence: 99%
“…For example, in randomized trials both iso-and hyperoncotic HES solutions have increased the incidence of ARF in patients with severe sepsis or septic shock [5]. Conversely, in model system studies and clinical trials albumin solutions, including hyperoncotic albumin, have displayed renoprotective activity [1,4]. Further mechanistic studies are needed to define more precisely the effects of colloids on the kidney.…”
mentioning
confidence: 99%